Education for special learner populations challenges for teacher education - Lasam, Gloria Z.; National Congress on Teacher Education (1989 : University of the Philippines, Diliman, Quezon City).
This paper focused on the multicultural minorities, who lived in abject poverty, far from civilization, and not yet found a breakthrough in their ancient ways. These groups of people whose needs and interest are not necessarily the same as ours; whose culture and lifestyle resist the lure of civilized life ,as they continually remind us of the increasing inequality and parities in the delivery of services and allocation of resources. The research did not touch the lives of the ethnic tribes, but opened to us educators, the possibilities for interventions.
Keywords: Minorities -- Education -- Philippines -- Cagayan Valley Region; Ethnic groupsEducation -- Philippines -- Cagayan Valley Region; Teachers -- Training of -- Philippines -- Cagayan Valley Region; Teaching -- Philippines -- Cagayan Valley Region -- Aids and devices